Towards Institutionalization of One Health in Eastern and Southern Africa - Richards, Shauna; Knight-Jones, Theodore J.D.; Angombe, Simon; Becker, J.; Bukachi, Salome R.A.; Chirenda, Joconiah; Araújo, Lucinda de; Nys, Hélène M. de; Desta, Hiwot; Fafetine, José; Fèvre, Eric M.; Freeman, Rachel J.; et al. (CAB International, 2024)
The integration of One Health (OH) approaches, principles, and ethos within international organizations and public sectors’ national health and environmental structures is a long process that requires both institutionalization and operationalization. Within the framework of a development project covering 12 countries in Eastern and Southern Africa, an innovative process to institutionalize OH approaches and principles at the national level is presented. Supported by international research and technical organizations, national higher education institutions were empowered to assist relevant ministries and stakeholders in their roadmap towards the integration of OH approaches and principles. A rapid OH assessment tool was designed to understand the existing OH stakeholders, governance structures, and gaps in the implementation of OH in each country. This provided evidence for developing plans for furthering the country’s goals towards institutionalizing OH and was implemented through a stakeholder, demand-driven process. After close to 2 years of implementation, five key insights for OH institutionalization developed: (1) utilizing higher education ‘multiplier’ institutions for intersectoral cohesion and action; (2) emphasizing participatory design driven by demand; (3) having a flexible project framework to ensure national needs are met with timing adapted to local administrative and political rhythms; (4) promoting cross-country learning opportunities that offer peer-to-peer buy-in, trust; and (5) the need for soft skills training in OH for better intersectoral collaboration.